CUSTOMER EXPERIENCE AND SATISFACTION WITH DIGITAL BANKING SERVICES - Trani, Ai Huu; Tran, Dung Anh (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
Digital banking services bring many benefits to banks such as reducing the number of employees, branches, increasing the number of transactions... thereby reducing costs and increasing profits. Research results show that (1) Brand trust, (2) Customer convenience (3) Customer satisfaction, (4) Digital banking innovation, (5) Digital banking service quality, (6) Employee engagement, (7) Risk perception, (8) Perceived value are important reasons importantly to accept retail banking customers